1997
DOI: 10.1287/mnsc.43.12.1645
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Impact on Process Output and Quality

Abstract: Our work represents one of the first attempts to assess the impact of IT (information technology) on both process output and quality. We examine the optical character recognition and barcode sorting technologies in the mail sorting process at the United States Postal Service. Our analysis is at the application level, and thus does not involve the aggregation of IT impact over multiple processes. We use data from 46 mail processing centers over 3 years to study the IT impact. We also use a set of factors in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 15 publications
4
106
0
2
Order By: Relevance
“…The following studies would support the results in the empirical study : Mukhopadhyay, Rajiv, and Srinivasan (1997) defend that ICT increases the quality of the service. Bharadwaj et al (1999) also show in an illustrative way, that some intangible values, coming from ICT investments, would have an impact in the improvement of some aspects: in the quality of products and services, in the relationship with the final customer.…”
Section: H2 the Implementation Of An Ita System Improves The Qualitysupporting
confidence: 63%
See 1 more Smart Citation
“…The following studies would support the results in the empirical study : Mukhopadhyay, Rajiv, and Srinivasan (1997) defend that ICT increases the quality of the service. Bharadwaj et al (1999) also show in an illustrative way, that some intangible values, coming from ICT investments, would have an impact in the improvement of some aspects: in the quality of products and services, in the relationship with the final customer.…”
Section: H2 the Implementation Of An Ita System Improves The Qualitysupporting
confidence: 63%
“…The obtained results in this empirical study would be identified with a group of previous literature as for example. Mukhopadhyay et al (1997) that state that ICT increases the quality, and this increase offers at the same time an increase in productivity, and Bharadwaj et al (1999) that state how some intangible values, coming from ICT investments have a tendency to improve the quality of products, services, and customer attention. Porter (2001) also stresses how the implementation of ICT in organizations improves the quality and the service differentiated to the customer and Pérez (2001) in a specific work on public transport affirms that the implementation of ICT in firms improves the quality of service.…”
Section: Figure 7 Results In the Estimations Of The Quality Indexmentioning
confidence: 99%
“…Another recent study at the application level of a firm in the U.S. Postal Service found that investments and use of IT led to higher output of mail-sorting facilities [49]. This points to a key nuance that investments in IT have to be coupled with the actual use of IT.…”
Section: Literature and Research Propositionsmentioning
confidence: 99%
“…Furthermore, three or five data points may not be sufficient to establish a trend for IT payoff, especially when there are lag effects resulting from IT investment and noticeable payoffs. A data set that includes quarter-level data for three to five years, combined with the corresponding control variables, would flimish sufficient data points and provide meaningful results [49].…”
Section: Literature and Research Propositionsmentioning
confidence: 99%
“…Although some empirical studies demonstrate a positive relationship between IT and success variables (Bharadwaj, Bharadwaj, and Konsynski, 1999;Brynjolfsson and Kemerer, 1996;Devaraj and Kohli, 2000;Dewan and Min, 1997;Mukhopadhyay, Rajiv, and Srinivasan, 1997) overall results are contradictive and result the so called "IT paradox" (Brynjolfsson, Hitt, and Yang, 2002).…”
Section: It Business Value and It Usagementioning
confidence: 99%